Intergenerational mobility and student loans - Ryota Nakano (Osaka University, Institute of Social and Economic Research (ISER), 2024)
The decision of whether and how much to borrow from the credit market in order to finance education costs depends crucially on parental investment in education. This study constructs a simple two-period overlapping generations model incorporating both educational investment from parents and educational borrowing. The analysis shows that in the case where educational investment from parents and educational borrowing are substitutive, the relaxation of the borrowing constraint improves intergenerational mobility. In the complementary case, the relaxation of the borrowing constraint may impair intergenerational mobility. Implications differ depending on whether the relationship between parental investments and borrowings is substitutive or complementary.
Keywords: I22; I24; J62; 330; Educational borrowing; Intergenerational mobility; Education